A comparison between amblyopic and fellow eyes in unilateral amblyopia using spectral-domain optical coherence tomography - Araki S (Dove Medical Press, 2014)
Syunsuke Araki,1 Atsushi Miki,1,2 Tsutomu Yamashita,1,2 Katsutoshi Goto,1,2 Kazuko Haruishi,1 Yoshiaki Ieki,1 Junichi Kiryu1 1Department of Ophthalmology, Kawasaki Medical School, Kurashiki, Japan; 2Department of Sensory Science, Faculty of Health Science and Technology, Kawasaki University of Medical Welfare, Kurashiki, Japan Purpose: To compare the macular retinal thickness and characteristics of optic nerve head (ONH) parameters in amblyopic and fellow eyes in patients with unilateral amblyopia.Patients and methods: A total of 21 patients with unilateral amblyopia (14 patients with anisometropic amblyopia, four patients with strabismic amblyopia, and three patients with both) were examined using spectral-domain optical coherence tomography. The mean age of the patients was 8.5±3.5 years. The examined parameters included the mean macular (full, inner, and outer), ganglion cell complex and circumpapillary retinal nerve fiber layer (cpRNFL) thicknesses, and ONH parameters (rim volume, nerve head volume, cup volume, rim area, optic disc area, cup area, and cup-to-disc area ratio).Results: The amblyopic eyes were significantly more hyperopic than the fellow eyes (P<0.001). Among the macular retinal thickness parameters, the cpRNFL thickness (P<0.01), macular full retinal thickness (3 mm region) (P<0.01), and macular outer retinal thickness (1 and 3 mm regions) (P<0.05) were significantly thicker in the amblyopic eyes than in the fellow eyes, while the ganglion cell complex thickness, macular full retinal thickness (1 mm region), and macular inner retinal thickness (1 and 3 mm regions) were not significantly different. Among the ONH parameters, the rim area was significantly larger and the cup-to-disc area ratio was smaller in the amblyopic eyes than in the fellow eyes (P<0.05). None of the other ONH parameters were significantly different between the investigated eyes. The differences in the cpRNFL thickness and macular outer retinal thickness in the 1 mm region were significantly correlated with the difference in axial length (P<0.05, r=–0.48; P<0.01, r=–0.59, respectively) and refractive error (P<0.05, r=0.50; P<0.01, r=0.60, respectively). The other parameters were not significantly related to the difference in axial length, refractive error, or best corrected visual acuity.Conclusion: We found significant differences in some of the morphological measurements between amblyopic and fellow eyes that appear to be independent of abnormalities in the visual cortex. Keywords: anisometropic amblyopia, strabismic amblyopia, ganglion cell complex thickness, macular retinal thickness, peripapillary retinal nerve fiber layer thickness